KONTRIBUSI TRANSPARANSI BUDAYA BERSIH PERUSAHAAN, STRUKTUR KEPEMILIKAN DAN NILAI PERUSAHAAN PADA INDUSTRI PERBANKAN - Budi Her Utomo, - (2014)
This study aims to identify and analyze the implementation of corporate governance, family ownership structure or the institutional ownership of company value in the banking industry in Indonesia. Corporate governance as measured using the standard index of corporate governance in OECD and IICG SSR study (2006), adjusted by Bank Indonesia Regulation No.. 8 / 4 / / PBI/2006 about the implementation of corporate governance in commercial banks. Ownership structure is measured by the total percentage of ownership of shares owned by family ownership and institutional ownership, and value the company based on market based on PBV, because in this study there is a sensitivity test of company operations dependent variable values, hence in this study will measure the company value based on accounting- based ROE. In this study, there were the controlling variables consisting of firm growth, MVE and company size. Equation models and hypothesis testing using a statistical model using multiple regression and ordinary least square. Samples are in the industrial banking companies listed in Indonesia Stock Exchange as many as 26 banks in the period 2007-2012 Based on the results of testing hypothesis to conclusion that corporate governance by institutional ownership has the ability to apply the CG better, so that is expected to further increase the performance of the bank and can minimize the risks being faced, which in turn could enhance shareholder value. Implementation of Corporate Governance is closely related to the company values that can enhance the company image in the banking industry. Corporate Governance of Banks that practice, will further enhance the performance of the bank and can minimize the risks faced, and can protect the interests of shareholders. However, management at the bank with a dominant family ownership is not interested in long-term benefits of implementing corporate governance, corporate governance and conduct based solely on compliance with regualasi Bank Indonesia regarding the application of corporate governance.